Analisis Kepuasan Pelayanan dan Loyalitas Pelanggan dengan Menggunakan Metode Servqual, IPA, dan QFD di Terminal Teluk Lamong - Dafazal Saffan; Bambang Syairudin; Fuad Achmadi (UNUSA Press, 2018)
Service is a very important element in the effort to increase customer satisfaction and loyalty. Basically, the position of these services is a supporting factor to the service activities of PT Terminal Teluk Lamong. The number of service users who did online booking in counters and complaints in the services provided to encourage researchers to conduct research. The study population was a customer Terminal Teluk Lamong the number 312 company. The total sample of 75 respondents using the sampling method used is purposive sampling and Slovin formula. The analysisused in knowing the fit between the expectations and reality, used models Cartesian diagram. The results of the Cartesius diagram is processed with the House of Quality in QFD. The results of the analysis of SERVQUAL and QFD shows that five (5) top priority in efforts to improve customer satisfaction Terminal Teluk Lamong, namely: (1) evaluate the SOP of the process behandle, (2) adding personel to the clerk TKBM in behandle locations, (3) provide specialized training for officersat the behandle location, (4) Trying to establish a communication network with the Customs, if the service users experiencing problems in the management of NPE, and (5) Increases forklift unit if necessary.